Liver Metastasis in Advanced Ovarian Cancer after Chemotherapy: A Case Report - Virgusrudhina, Mitra; Muhammad, Syamel; Antonius, Puja Agung (Syntax Corporation, 2024)
Ovarian cancer is the most lethal disease among gynecologic malignancies; about 1/4 of ovarian cancer patients are in stage IV when diagnosed. Based on the data of Globocan, there were 295,414 newly diagnosed ovarian cancer patients and 184,799 deaths registered in 2018. For ovarian epithelial cancer patients with stage IV disease, the mean overall survival (OS) is around 20 months, and the 5 year-OS is about 20%. About 1 in 5 patients with advanced-stage ovarian cancer have hepatobiliary involvement. The study on HGSOC aims to understand the molecular and genetic features, diagnosis, and prognosis of HGSOC, as well as its response to therapy. The method involves analyzing the genetic traits, chromosomal instability, and dysregulation of signaling pathways associated with HGSOC, as well as the detection of stemness and EMT levels in response to chemotherapy and radiation therapy. The results highlight the unique characteristics of HGSOC, such as nearly universal mutation in and dysfunction of p53, genomic instability, and the role of cancer stem cells and EMT in chemo- and radiation resistance. The implication of the study is the need for a better understanding of the molecular basis of HGSOC for improved diagnosis, prognosis, and treatment strategies.